Mobile data loss : threats and countermeasures - Raggo, Michael T. (Waltham, MA : Syngress, 2015)
The mobile threat landscape is evolving bringing about new forms of data loss. No longer can organizations rely on security policies designed during the PC era. Mobile is different and therefore requires a revised approach to countermeasures to mitigate data loss. Understanding these differences is fundamental to creating a new defense-in-depth strategy designed for mobile. Mobile Data Loss: Threats & Countermeasures reviews the mobile threat landscape using a hacker mind-set to outline risks and attack vectors that include malware, risky apps, operating system compromises, network attacks, and user behaviours. This provides the basis for then outlining countermeasures for defining a holistic mobile security methodology that encompasses proactive protections, response mechanisms, live monitoring, and incident response. Designing a comprehensive mobile security strategy is key. Mobile Data Loss: Threats & Countermeasures outlines the threats and strategies for protecting devices from a plethora of data loss vectors.
Machine generated contents note: ch. 1 Preparing for Generation Mobile -- Introduction -- The Problem -- What's Different about Mobile? -- Secrets to Mobile Data Loss Prevention Success -- Summary -- ch. 2 Understanding Mobile Data Loss Threats -- Mobile Threat Vectors -- Mobile OS Compromise -- Malware and Risky Apps -- User Data Loss -- Mobile Network Threats -- Summary -- ch. 3 Mobile Security Countermeasures -- Mobile OS Compromise -- Malware and Risky Apps -- Access Control and Conditional Access -- Lockdowns and Restrictions -- Live Monitoring, Audit Logs, Events, and Reporting -- Incident Response and Forensics -- Mobile Device Updates and Patching -- Wearables -- Device Encryption and Containers -- PINs, Passwords, and Passcodes -- Cloud -- File-Level Security -- Summary -- ch. 4 Ensuring Mobile Compliance -- PCI -- HIPAA -- CJIS -- Summary -- ch. 5 Developing Your Mobile Device Security Strategy -- Proactive Controls -- Reactive Controls and Protections -- Mobile Data Loss Threats and Countermeasures Flow -- Mobile DLP Methodology -- Futures.
Description based on print version record.
Keywords: Mobile communication systems -- Security measures; Data protection; Mobile computing -- Security measures; Computer security; Computer security; Data protection; Electronic books